2018
DOI: 10.1088/1612-202x/aae222
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical behavior of maximal steered coherence and concurrence under decoherence

Abstract: In this work, by employing quantum steering ellipsoid (QSE) pictures, we investigate the dynamical characteristics of maximal steered coherence (MSC) and concurrence for an arbitrary Bell-diagonal state when the qubit-system suffers from canonical noisy channels, such as phase damping, bit flip and bit-phase flip channels. It has been found that the MSC is equal to the longest semiaxis length of the QSEs. Remarkably, the QSEs have an invariant semiaxis length under these mentioned unital channels. The dynamica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The sufficient and necessary condition for a QSE to denote a bipartite state was derived by Milne et al [41] It is worth mentioning that the QSE provides an intuitive depiction and indication for quantum correlations. Examples include steered coherence, [42][43][44] discord, [38,[45][46][47] entanglement [38,41,48] and EPR steering. [49][50][51][52][53][54] Zhang et al [55] experimentally verified the QSE of two-qubit states and also demonstrated volume monogamy relations of the QSE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sufficient and necessary condition for a QSE to denote a bipartite state was derived by Milne et al [41] It is worth mentioning that the QSE provides an intuitive depiction and indication for quantum correlations. Examples include steered coherence, [42][43][44] discord, [38,[45][46][47] entanglement [38,41,48] and EPR steering. [49][50][51][52][53][54] Zhang et al [55] experimentally verified the QSE of two-qubit states and also demonstrated volume monogamy relations of the QSE.…”
Section: Introductionmentioning
confidence: 99%
“…However, these efforts are limited to inertial systems. [42][43][44][45]57] The non-inertial frame provides nontrivial tools for understanding relativistic quantum information and black holes, and is a rapidly developing field. [58] Relevant explorations in the non-inertial frame have been widely carried out.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely studied the effect of decoherence on entanglement both in theory and experiment [22,23,[26][27][28]. However, there are only a few theoretical studies on other nonlocal quantum correlations [34][35][36][37]. These studies deal with the entanglement sudden death (ESD) [22,23,26,27] and Bell nonlocality sudden death (BNSD) [37], however, the study of EPR steering sudden death (SSD) is still missing.…”
Section: Introductionmentioning
confidence: 99%